A Synopsis of Cattle Performance In Zimbabwe’s ‘Initial’ Resettlement Areas After Land Reforms And Redistribution - Chinuwo, T.; Mugabe, P.H.; Mpofu, M.I.D.T.; Mulugeta, M.S.D.; Timpong-Jones, E.C. (Bulletin of animal health and production in Africa, 2009)
Cattle performance was monitored over a two year period in a resettlement area, a spatial land-use product of Zimbabwe’s land reforms post-independence. A total of 30 farmers each owning at least 5 cattle in 3 selected villages of a 20 village resettlement scheme were targeted for the study. Participating village rangelands were assessed monthly for biomass yield in different physiognomic cover classes. Cattle in the study were monitored over a two year period for reproduction (calving rate and frequency, re-calving rates) and exit records (sales, slaughters, deaths, exchange, and buy-in) under farmer management conditions. Cattle weights, exit and reproduction records were analyzed as measures of performance. The study found low to medium calving rates (25-40%) and low re-calving rates (16 -26%), with diminished nutrition and low off-take (7.3% to 18.7%) as major impediments to cattle performance. Monthly cattle weights fluctuated with quantity of available grazing biomass, and were lowest during the dry months (September to December). Cows and heifers were affected more by diminished nutrition than steers. The study concluded that improving nutrition, increasing off-take and possibly availing bulls in resettlement areas were appropriate actions to increase cattle performance in the short to medium term, complimented by adequate veterinary practices.
Research Article
Keywords: Cattle performance; farmers; physiognomic; nutrition